The structures underlying soliton solutions in integrable hierarchies - Ferreira, L. A.; DOlivo, J. C.; KleinKreisler, M.; Mendez, H. (Aip Press, 1997)
We point out that a common feature of integrable hierarchies presenting soliton solutions is the existence of some special ''vacuum solutions'' such that the Lax operators evaluated on them, lie in some abelian subalgebra of the associated Kac-Moody algebra. The soliton solutions are constructed out of those ''vacuum solitons'' by the dressing transformation procedure.